Intrinsic compression characteristics of an expansive clay from Western Australia - Habibbeygi, Farzad; Nikraz, Hamid; Chegenizadeh, Amin (The Geomate International Society, 2017)
Intrinsic compression behaviour of an expansive clay from Western Australia is investigated using the intrinsic framework in this study. Oedometer results conform with the intrinsic concept at post-yield phase. However, there is a great impact of initial water content on the compression curves at pre-yield stage. It specifies that there is an initial structure similar to a natural clay structure which resists applied forces at this phase and it is related to the amount of initial water content at the preparation stage. Nonetheless, this interparticle bonding is demolished when vertical stress becomes greater than remoulded yield stress. The findings also show that the remoulded yield stress of a reconstituted clay decreases non-linearly with the increase of initial water content, and is remarkably affected by its clay mineralogy. The remoulded yield stress of a soil with the predominant clay of smectite is far greater than those of other clay minerals despite having the same normalised initial void ratio value (e0/eL). Moreover, remoulded yield stress of an expansive soil with main clay mineral of smectite decreases more abruptly than for other clay minerals reported in the literature. Reconstituted compression indexes (C*c,e100*) for clays with a considerable amount of smectite are also greater than respective values for other clay minerals.